The cost of mass gatherings during a pandemic - Ludovic Phalippou; Dayin Zhang (SSM: Population Health, 2023)
In June 2020, the U.S., unlike other regions of the world, faced a surge in cases of COVID-19. Immediately prior to this wave of cases, the largest mass protests in U.S. history took place. We show that when holding other factors constant, COVID-19 cases increased most in places where more demonstrations occurred. We exploit variation in rainfall during the protest period as an exogenous source of variation in attendance. We find that good weather coincides with both more people protesting and more subsequent COVID-19 cases and deaths. Mass gatherings during a pandemic thus lead to more contraction and fatalities of COVID-19, and we quantify these effects.